Seismic Performance of Irregular RCC Structures with Floating Columns: Effects of Shear Walls and Bracings Using Time History Analysis - Dongre, Ritika; Hora, M.S. (Engineering Research: Perspectives on Recent Advances Vol. 2, 2025)
The present research work presents a time history analysis of an irregular (G+8) RCC building frame to investigate the effect of shear walls, bracings and floating columns on its seismic performance. The research explores various seismic intensities and ground motion characteristics to assess the structural response. The comparative analyses are carried out for a building frame with and without shear walls, and the inclusions of bracings and floating columns at different floor levels are presented. The evaluation of inter-storey drift, storey shear, storey displacement and time period are made to assess the structural performance, seismic vulnerability and building resilience against seismic hazards. The research findings reveal that the inclusion of shear walls, bracings, and irregularities like floating columns in an RCC building significantly enhances seismic resilience by reducing lateral displacements, and drifts, and hence effectively distributing lateral forces for better structural performance. This research aims to ensure safer and more resilient structures in seismic-prone regions.